KOMPETENSI SUMBER DAYA MANUSIA, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH, PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN , DAN PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH PADA SATUAN KERJA PERANGKAT DAERAH KOTA SEMARANG - Mega Andani Putri; Maryono Maryono; Batara Daniel Bagana (Faculty of Economic and Business Universitas STIKUBANK, 2017)
This study aims to examine and analyze the influence of competence of human resources, regional financial accounting system, government accounting standards, internal control, the quality of local financial statements at the Regional Work Unit Unit in Semarang City. This study uses primary data obtained by spreading the questionnaire in the Regional Work Unit Unit of Semarang City. Respondents in this research are Echelon III and Echelon IV. Sampling method using purposive sampling with the help of software SPSS version 16. The result of this research stated that the competence of human resources has no effect on the quality of regional financial report, while the variables of government accounting system, the variable of financial accounting system of the region and internal control influence to the quality of regional financial report. Keywords: quality financial reporting areas, the competence of human resources, financial accounting systems of the region, government accounting standards,internal control